Characteristics of Chemical Composition and Particle Size Distribution from Real Coal-fired Circulating Fluidised Bed (CFB) Boiler - Xin Du; Jianhui Wu; Yingze Tian; Yufen Zhang; Baoshuang Liu; Yinchang Feng (Aerosol and Air Quality Research)
Abstract The chemical component (element, ion, and carbonaceous aerosols) behaviour in particle size distributions (PSDs) was studied by determining the particulate matter (PM) emitted from the circulating fluidised-bed (CFB) combustion flue gas. Four CFB coal-fired boilers were employed in power plants. The actual particle mass percentages and PSDs were measured using an electrical low-pressure impactor (ELPI). Ion concentrations (SO42–, Cl–, NO3–, Na+, NH4+, Mg2+, K+ and Ca2+) were determined by ion chromatography (IC), elements (Al, Ca, Cr, Cu, Fe, K, Mg, Na, Ni, Pb, S, Si, Ti and Zn) were determined by inductively coupled plasma-mass spectrometry (ICP-AES), and the carbonaceous content (OC1, OC2, OC3, OC4, EC1, EC2 and EC3) was measured by thermal optical analysis. Significant differences were observed in the four boilers for PSD. Chemical species in particulate matter mainly concentrated in sizes 0.1–2.5 µm in aerodynamic diameter. In this work, the mass percentage of Ca, Ca2+, SO42–, NH4+ and OC were significantly high in different particle size regions. The mass concentrations of elements, ions, and carbonaceous aerosols in various sizes displayed trimodal or bimodal distributions; however, the peaks of mass concentrations of chemical species in different particle sizes varied greatly. Furthermore, the size distribution of chemical species was influenced by the pollution control device employed, and the same chemical species showed a marked difference among coal-fired boiler equipped with different pollution control devices. In addition, it was observed that the ratio of OC to EC was related to dust-cleaning method.